1999
DOI: 10.1139/z99-169
|View full text |Cite
|
Sign up to set email alerts
|

Comparative body composition strategies of breeding and nonbreeding female caribou

Abstract: We evaluated the effects of season and reproductive status on body fat and body protein masses of freeranging female barren-ground caribou (Rangifer tarandus granti). Body fat mass fluctuated markedly during the year (by a factor of at least 2) in both reproductive classes, but whereas maximum fatness occurred in autumn (September-November) in nonbreeding females, it did not occur until late winter (March-April) in breeding females. Seasonal changes in dry body protein mass were relatively modest, with annual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 43 publications
2
45
0
Order By: Relevance
“…Pregnant females are likely most sensitive to these types of restrictions during the third trimester when physiological demands of fetal growth are the highest. Monitoring changes in body protein, however, is challenging because of the relatively small changes that occur throughout the year (approx 9.5-11.2% of body mass for breeding female caribou, Chan McLeod et al, 1999). Recent use of nitrogen isotopes in snow urine to assess nitrogen balance in late winter (Parker et al, 2005;Barboza & Parker, 2006) is promising, but this technique requires validation in wild populations of caribou.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pregnant females are likely most sensitive to these types of restrictions during the third trimester when physiological demands of fetal growth are the highest. Monitoring changes in body protein, however, is challenging because of the relatively small changes that occur throughout the year (approx 9.5-11.2% of body mass for breeding female caribou, Chan McLeod et al, 1999). Recent use of nitrogen isotopes in snow urine to assess nitrogen balance in late winter (Parker et al, 2005;Barboza & Parker, 2006) is promising, but this technique requires validation in wild populations of caribou.…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing that the deposition and mobilization of fat varies with age (Dauphiné, 1976;, previous demands of reproduction (ChanMcLeod et al, 1994), and across the winter season (Thomas & Kiliaan, 1998;Chan-McLeod et al, 1999), ultrasonography can be used as a non-invasive technique in the field to assist in evaluating nutritional condition of caribou. Similar to data collected from carcass evaluations in previous studies on barrenground caribou (e.g., Dauphiné, 1976;Thomas & Kiliaan, 1998), the non-pregnant woodland caribou in our sample had less rump fat than pregnant individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fat reserves vary independent of protein among populations and are dependent on reproductive history of the female (Parker et al, 2005(Parker et al, , 2009. Although body protein is often thought to be only poorly mobilized, data from Rangifer populations would challenge this assumption since the seasonal change in body protein is about 26-42% (Huot 1989;Gerhart et al, 1996;Chan-McLeod et al, 1999) giving a LPR of 3-6 kg. e 4.6 kg protein loss (Fig.…”
Section: De Ning Labile Fat and Protein Reservesmentioning
confidence: 99%
“…In particular, Skogland (1983) argued that morphology was density-dependent and related to the factors limiting population growth. Both Skogland (1983) and Chan-McLeod et al (1999) reported that female R. tarandus that had reproduced successfully were significantly lighter the following winter than those that had not. Here, I present the first description of Woodland Caribou from central Saskatchewan and a discussion of their morphology relative to limiting factors.…”
mentioning
confidence: 99%